Solidarity and alignment in nurse practitioner–patient interactions. (August 2014) - Defibaugh, Staci
This article focuses on how solidarity is negotiated in interactions during medical visits between nurse practitioners (NPs) and patients. Drawing on data from ethnographic field notes, audio-recorded interactions and interviews involving one NP and 20 patients, the article outlines ways in which the NP creates a sense of solidarity by lessening the social distance between herself and her patients. These attempts at solidarity do not correlate with what has been noted in previous studies of medical visits involving medical doctors (MDs) and may represent a difference in how both the NP and the patients view the NP as a mid-level provider. As NPs are taking on a more prominent role in the healthcare landscape, it is important to understand what the interactional norms are and how these may deviate from the norm set by MDs.